A numerical time integration mrthod for nonlinear seismic response analysis of roller-compacted concrete dams - Pour, Parviz Moradi (2010)
Dam is used as a multi-purpose infrastructure for water supply, irrigation, flood control, and hydropower. The application of roller compacted concrete (RCC) technology to dam construction was originated in the United States about three decades ago. To ensure the safety of life and public property and to preserve the environmental downstram of the dam, comprehensive studies are warranted. The critical issues in this field are thermal and earthquake analysis of the dam-foundation system, which leads to crack prediction in the dam body as well as sliding and debonding at dam foundation interface. This study deals with the two objectives; to propose a new numerical method and to apply the method for dynamic analysis of the Kinta RCC dam.The first objective is to propose a new method with higher accuracy and stability as well as less computational cost. The proposed method involves mathematical formulations and general equilibrium equations for structural dynamics. The acceleration between two consequent time steps was assumed by a second order parabolic curve. Then, Taylor’s series were used in mathematical formulations for any response. Finally, mathematical and structural dynamics equations were combined. The application of the proposed method has been established by a few examples to illustrate the accuracy of the proposed method for analysis of any stracture. Based on this objective, the following conclusions can be drawn: i) The proposed method is capable of capturing the seismic structural responses of any SDOF and MDOF systems more accurately than Newmark’s method. ii) The proposed method is more stable than Newmark”s method and is able to analyze the structure in fewer numbers of iterations or computation cycles, hence less time-consuming. The second primary objective deals with the structural response of Kinta RCC dam as one of the two RCC dams in Malaysia. To achieve this objective, the finite element method has been selected. An existing finite element program for two-dimensional analysis has been modified to include the proposed method in the program. This study is also to improve the physical modeling of plane strain problems such as Kinta RCC dam. The isoparametric elements have been employed to represent the dam body, foundation sections, and thin layer interface elements. The nonlinearity of the dam body concrete and foundation has been taken into account by employing the crack constitutive model and nonlinear elasto-plastic model respectively. Finally, the finite element model was nonlinearly analyzed under Malaysian seismic excitations using the developed FEM program. i) The results show that the yielding of thin layer interface elements occurs before the dam foundation and RCC material, and it starts by a slipping mode at the interface beween foundation and dam body. ii) From the seismic fracture analysis of Kinta RCC dam, it was observed that the values of acceleration and stresses of the system are higher than those found by previous researchers. This indicates a fast occurrence of fracture in both thin layer interface elements and dam body.